2003
DOI: 10.1002/ijc.10950
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of invasion and peritoneal carcinomatosis of ovarian cancer cell line by overexpression of bikunin

Abstract: Bikunin (bik), a Kunitz-type protease inhibitor, also known as urinary trypsin inhibitor, is proposed as a main participant in the inhibition of tumor cell invasion and metastasis, possibly through the direct inhibition of cell-associated plasmin activity and suppression of urokinase-type plasminogen activator (uPA) mRNA expression. In the present study, we transfected the human ovarian carcinoma cell line HRA, highly invasive cells, with an expression vector harboring a cDNA encoding for human bik. Our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 41 publications
(68 reference statements)
5
75
0
Order By: Relevance
“…Devoogdt et al (2003) demonstrated that transfection of the human SLP1 cDNA into Lewis lung carcinoma cells resulted in increased tumourigenicity and lung-colonising potential. In contrast, however, the protease inhibitor SPINT2 was shown to reduce the metastatic potential of ovarian cancer cells (Suzuki et al, 2003). This result highlights the complexity of defining the The score derived from this analysis using a significance threshold of 3.1 is shown.…”
Section: Discussionmentioning
confidence: 83%
“…Devoogdt et al (2003) demonstrated that transfection of the human SLP1 cDNA into Lewis lung carcinoma cells resulted in increased tumourigenicity and lung-colonising potential. In contrast, however, the protease inhibitor SPINT2 was shown to reduce the metastatic potential of ovarian cancer cells (Suzuki et al, 2003). This result highlights the complexity of defining the The score derived from this analysis using a significance threshold of 3.1 is shown.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, bikunin, another Kunitz-type protease inhibitor, also inhibits cell invasion, possibly through direct inhibition of cell-associated plasmin activity. 32 Finding that overexpression of TFPI-2 increased apoptosis, both for ECs in vitro and for cells in Matrigel implants in vivo, indicates that TFPI-2 may also protect against aberrant neovessel formation through proteolysis-independent mechanisms. It remains to be established whether the process may also involve regulation of gene expression of proteins like VEGF-C, VEGFR1, or ECM components.…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture-The ovarian cancer cell line, HRA, was grown in Dulbecco's modified Eagle's medium (Sigma) supplemented with 10% (v/v) fetal bovine serum, penicillin (100 units/ml), and streptomycin (100 g/ml) in a 5% CO 2 atmosphere with constant humidity (18). SKOv-3 and OVCAR-3 ovarian cancer cells were obtained from the American Type Culture Collection (Manassas, VA).…”
Section: Methodsmentioning
confidence: 99%